Legal regime of water management facilities - Szalma, József (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
The paper analyzes the legal regime of water management facilities in the light of Serbian, foreign and European law. Different divisions of water management facilities are carried out (to public and private ones, natural and artificial ones, etc.), with determination of their legal relevance. Account is taken of the issue of protection from harmful effects of waters to such facilities, as well. The paper points also to rules on the water management facilities, from acts of planning, to individual administrative acts and measures for maintenance of required qualitative and quantitative condition of waters, depending on their purpose (general use or special, commercial use o waters). Albeit special rules on water management facilities exist, due to the natural interlocking between all the components of the environment (water, air and soil), a comprehensive approach is required. A reference is made to other basic principles of protection of water management facilities as well, such as the principle of prevention, principle of sustainable development and the principle “polluter pays”. The last one represents the achievement of contemporary law, which deviates from the idea accepted in the second half of 20th century that supported the socialization of risk from harmful effects of waters.